2000
DOI: 10.1161/01.res.86.7.816
|View full text |Cite
|
Sign up to set email alerts
|

Nerve Sprouting and Sudden Cardiac Death

Abstract: The factors that contribute to the occurrence of sudden cardiac death (SCD) in patients with chronic myocardial infarction (MI) are not entirely clear. The present study tests the hypothesis that augmented sympathetic nerve regeneration (nerve sprouting) increases the probability of ventricular tachycardia (VT), ventricular fibrillation (VF), and SCD in chronic MI. In dogs with MI and complete atrioventricular (AV) block, we induced cardiac sympathetic nerve sprouting by infusing nerve growth factor (NGF) to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
367
4
4

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 387 publications
(400 citation statements)
references
References 31 publications
20
367
4
4
Order By: Relevance
“…Although the present study confirms peri-infarct hyperinnervation (Cao, et al, 2000a;Cao, et al, 2000b), other studies have reported reduced cardiac sympathetic innervation after infarction (Barber, et al, 1983;Igawa, et al, 2000;Li, et al, 2004). These differences may be related to the extent of infarction as larger infarcts can result in frank congestive heart failure, and this has been linked to cardiac NGF depletion and diminished sympathetic axon density (Kaye, et al, 2000;Qin, et al, 2002).…”
Section: Selectivity Of Post-infarct Hyperinnervationsupporting
confidence: 59%
See 1 more Smart Citation
“…Although the present study confirms peri-infarct hyperinnervation (Cao, et al, 2000a;Cao, et al, 2000b), other studies have reported reduced cardiac sympathetic innervation after infarction (Barber, et al, 1983;Igawa, et al, 2000;Li, et al, 2004). These differences may be related to the extent of infarction as larger infarcts can result in frank congestive heart failure, and this has been linked to cardiac NGF depletion and diminished sympathetic axon density (Kaye, et al, 2000;Qin, et al, 2002).…”
Section: Selectivity Of Post-infarct Hyperinnervationsupporting
confidence: 59%
“…NGF is a potent growth and survival factor for sympathetic neurons (Korsching and Thoenen, 1985;Glebova and Ginty, 2004). Recent evidence indicates that NGF expression is up-regulated in the region of the infarction (Hiltunen, et al, 2001;Zhou, et al, 2004), and infusion of NGF into the stellate ganglion results in cardiac hyperinnervation in canine hearts (Cao, et al, 2000b). However, the cell types involved in post-infarct cardiac NGF production and the neural selectivity of the response are not well defined.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, NGF infusion to the left stellate ganglion resulted in nerve sprouting in normal dogs but did not cause ventricular arrhythmias or SCD. 46 A differential response of QTc and ventricular arrhythmia was seen when the left vs the right stellate ganglia were infused with NGF. Infusion into the left stellate ganglion cause sympathetic nerve sprouting on immunocytochemical staining in the left ventricle, with resulting QTc prolongation and sudden cardiac death in 50% of the experimental dogs.…”
Section: Myocardial Infarction Heart Failure and Sympathetic Innervmentioning
confidence: 99%
“…A study in dogs by Cao et al showed that injection of nerve growth factor in the vicinity of the left stellate ganglion increased the density of cardiac sympathetic fibres significantly and led to an increased incidence of ventricular dysrhythmias. 2 Later, Cao's group and others described similar cardiac sympathetic hyperinnervation in both adults and animals, including a history of ventricular arrhythmias and sudden cardiac death. [3][4][5] The patient described in this report suffered from both cardiac ischemia and obstructive sleep apnea, both of which lead to enhanced sympathetic output, nerve sprouting, and arrhythmogenic regional heterogeneities of sympathetic innervation.…”
Section: Discussionmentioning
confidence: 97%